To find y, we can use the Pythagorean theorem which states that in a right-angled triangle, the square of the length of the hypotenuse is equal to the sum of the squares of the other two sides.
So, we have:
y^2 + (3y-1)^2 = (3y+1)^2
Expanding and simplifying:
y^2 + 9y^2 - 6y + 1 = 9y^2 + 6y + 1
Combining like terms:
10y^2 - 6y = 9y^2 + 6y
Rearranging the equation:
10y^2 - 6y = 9y^2 + 6y
Subtracting 9y^2 from both sides:
y^2 - 6y = 6y
Subtracting 6y from both sides:
y^2 - 6y - 6y = 0
y^2 - 12y = 0
Factoring out y:
y(y - 12) = 0
Setting each factor to zero:
y = 0 or y = 12
Since the sides of a triangle cannot be zero, the only valid solution is y = 12.
The length of the sides of a right angled triangle are ym, (3y-1) m and (3y+1) m, find y
1 answer